2008
DOI: 10.1164/rccm.200701-031oc
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prognosis of Sustained Arrhythmias in Critically Ill Patients

Abstract: Sustained arrhythmias are observed in 12% of patients admitted to general ICUs. Ventricular arrhythmias increase the risk of death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
132
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 25 publications
11
132
3
1
Order By: Relevance
“…In general, patients with severe sepsis were more likely to be older in age, to have CHF, PVD, chronic obstructive pulmonary disease (COPD), DM and renal disease. Ischemic heart disease* 2,161,685 [7] 174,130 [10] CHF* 4,048,500 [14] 427,525 [24] PVD* 1,778,205 [6] 166,975 [10] Cerebrovascular disease* 1,952,330 [7] 144,150 [8] Chronic pulmonary disease* 6,493,627 [22] 495,285 [28] DM* 5,967,546 [21] 499,900 [28] DM with complications* 1,143,775 [4] 127,005 [7] Renal disease* 3,668,071 [13] 465,995 [27] Valvular heart disease* 1,717,610 [6] 131,640 [7] *Comparison between two groups done with Chi-square test. All P values significant at <0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients with severe sepsis were more likely to be older in age, to have CHF, PVD, chronic obstructive pulmonary disease (COPD), DM and renal disease. Ischemic heart disease* 2,161,685 [7] 174,130 [10] CHF* 4,048,500 [14] 427,525 [24] PVD* 1,778,205 [6] 166,975 [10] Cerebrovascular disease* 1,952,330 [7] 144,150 [8] Chronic pulmonary disease* 6,493,627 [22] 495,285 [28] DM* 5,967,546 [21] 499,900 [28] DM with complications* 1,143,775 [4] 127,005 [7] Renal disease* 3,668,071 [13] 465,995 [27] Valvular heart disease* 1,717,610 [6] 131,640 [7] *Comparison between two groups done with Chi-square test. All P values significant at <0.05.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to patients with preexisting A Fib, new onset A Fib has been associated with higher mortality rates (4). Furthermore, both atrial and ventricular arrhythmias have been associated with a higher incidence of neurologic compromise (22) and prolonged need for vasopressors (23).…”
Section: Discussionmentioning
confidence: 99%
“…First, the incidence of severe sepsis-associated, new-onset AF in our study (5.9%) was on the lower end of previously reported rates (6-20%). [2][3][4][5] AF incidence in our study may be lower because claims data are less sensitive for detecting new-onset AF as compared with the chart abstraction or prospective identification used in prior studies. Additionally, new-onset AF that occurred upon hospital admission in the setting of severe sepsis may be classified as "pre-existing AF" by the "present on admission" coding strategy used in our study, which might falsely lower the observed incidence of AF or bias outcome analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common arrhythmia to affect the critically ill. 1,2 Previous studies have demonstrated that 6-20% of patients with severe sepsis develop new-onset AF, suggesting that severe sepsis may be a predisposing factor for new-onset AF. [2][3][4][5] Whereas chronic AF is a major contributor to long-term disability and mortality, 6 the relation of newonset AF in severe sepsis to prognosis is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation